PENGARUH AKSESIBILITAS DAN CITRA DESTINASI TERHADAP NIAT BERKUNJUNG KEMBALI KE TELAGA TAMBING - HIDAYAT, TAUFIK NUR (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to simultaneously and partially determine and analyze the effect of accessibility and destination image toward the revisit to Tambing Lake. The variables of this research are accessibility (X1) and destination image (X2). While the dependent variable is the revisit (Y). This study used the research method of causal descriptive, with the sample size of 70 people. The sampling of this research used incidental sampling technique. The data analysis method in this research used multiple linear regression analysis method. The results showed that: 1). Accessibility and destination image simultaneously have significant effect on the revisit to Tambing Lake; 2). Accessibility partially have significant effect on the revisit to Tambing Lake; 3). Destination image partially have significant effect on the revisit to Tambing Lake.